Triplicate PCR reactions for 16S rRNA gene amplicon sequencing are unnecessary - Clarisse Marotz; Anukriti Sharma; Greg Humphrey; Neil Gottel; Christopher Daum; Jack A Gilbert; Emiley Eloe-Fadrosh; Rob Knight (BioTechniques)
Conventional wisdom holds that PCR amplification for sequencing should employ pooled replicate reactions to reduce bias due to jackpot effects and chimera formation. However, modern amplicon data analysis employs methods that may be less sensitive to such artifacts. Here we directly compare results from single versus triplicate reactions for 16S amplicon sequencing and find no significant impact of adopting a less labor-intensive single-reaction protocol.